Synthesis, Characterization of Various Substituted (E)-2-(2-butyl-5-chloro-4-((phenylimino)methyl)-1H-imidazol-1-yl)-N-(4-(3-oxomorpholino) phenyl)acetamide - Parmar, M. B.; Pandya, J. H.; Vara, M. K. (Journal of Scientific Research, 2023)
A highly efficient, convergent approach to the synthesis of various substituted (E)-2-(2-butyl-5-chloro-4-((phenylimino)methyl)-1H-imidazol-1-yl)-N-(4-(3-oxomorpholino)phenyl) acetamide analogues is described. Directed vilsmeyer formylation of methyl pentanimidate with glycine provides the key intermediate 2-butyl-5-chloro-1H-imidazole-4- carbaldehyde (INT-01). BCFI (INT-01) is a major active metabolite and the most significant intermediate of Losartan. Therefore, BCFI moiety has scope for good application in medicine. Morpholin-3-one derivative reacts with chloroacetyl chloride in presence of acetonitrile provides 2-chloro-N-(4-(3-oxomorpholino)phenyl)acetamide (INT-02). Reflux INT-01 with INT-02 in presence of acetonitrile and potassium carbonate allowed the preparation of the 2-(2-butyl-5-chloro-4-formyl-1H-imidazol-1-yl)-N-(4-(3-oxomorpholino) phenyl)acetamide with good yield. The reaction of 2-(2–butyl -5-chloro-4-formyl-1H-imidazol-1-yl)-N-(4-(3-oxomorpholino)phenyl)acetamide with substituted anilines in methanol and glacial acetic acid at room temperature gives a key intermediate for the synthesis of the M2-29V analogs with good yield. Novel analogs were characterized by 1H NMR, 13C NMR Mass Spectroscopy, and elemental analyses. Spectroscopic identification of intermediates and final products taken and favors the synthesis of M2-2901 to M2-2912.